Physical Activity, Sleep, and Nutrition Do Not Predict Cognitive Performance in Young and Middle-Aged Adults - Gijselaers, Hieronymus J. M.; Elena, Barberà; Kirschner, Paul A.; de Groot, Renate H. M. (Frontiers in Psychology, 2016)
Biological lifestyle factors such as physical activity, sleep and nutrition play a role in cognitive functioning. Research concerning the relation between biological lifestyle factors and cognitive performance is scarce however, especially in young and middle aged adults. Research has not yet focused on a multidisciplinary approach with respect to this relation in the abovementioned population, where lifestyle habits are more stable. The aim of this study was to examine the contribution of these biological lifestyle factors to cognitive performance. Path analysis was conducted in an observational study in which 1131 adults were analyzed using a cross-validation approach. Participants provided information on physical activity, sedentary behavior, chronotype, sleep duration, sleep quality, and the consumption of breakfast, fish, and caffeine via a survey. Their cognitive performance was measured using objective digital cognitive tests. Exploration yielded a predictive cohesive model that fitted the data properly, χ2/df=0.8, CFI=1.00, RMSEA<.001, SRMR=.016. Validation of the developed model indicated that the model fitted the data satisfactorily, χ2/df=2.75, CFI=0.95, RMSEA<.056, SRMR=.035. None of the variables within the BLFs were predictive for any of the cognitive performance measures, except for sedentary behavior. Although sedentary behavior was positively predictive for processing speed its contribution was small and unclear. The results indicate that the variables within the BLFs do not predict cognitive performance in young and middle aged adults.